Morbidity associated with osteoporosis significant in older men. Issue 4 (19th July 2022) - Grewal, Simran; Jawad, Ali S
Abstract : While osteoporosis is more common in women, older men are at greater risk of mortality in hospital from fracture; they also have more osteoporosis‐associated complications. Risk assessment, screening and treatment are therefore important for men as well as women.